The Mapping of Vegetation Density Changes Based on the Normalized Difference Vegetation Index Using Landsat OLI in The Coastal Region of Aceh Barat - Hayatun Maghfirah; Putri, Andriani (The Indonesian Journal of Computer Science, 2023)
Damage to coastal vegetation caused by the tsunami occurred rapidly, despite the critical role of vegetation in supporting life. Vegetation density is quantified through the use of an index known as the NDVI (Normalized Difference Vegetation Index). This index can be applied to assess changes in vegetation density over several years in coastal regions. The focus of this study was to analyze the changes in vegetation density along the coast of West Aceh in the years 2013, 2015, and 2020. The findings indicated that vegetation density in 2013 was notably low, with NDVI values falling within the range of -0.1495 to 0.1591, indicating a lack of vegetation. Furthermore, the percentage of areas with moderate vegetation density appears to have increased steadily year by year, with values of 26.73% in 2013, 27.50% in 2015, and a notable acceleration to 37.61% in 2020.